Toward an all-in-one recombinant adeno-associated virus vector for functionally ablating the prion gene using CRISPR-Cas technology - Claire Verkuyl; Ari Belotserkovsky; Thomas Zerbes; Declan Williams; Medha R. Krishnan; Sabrina Zhu; Sophie Grunnesjӧ; Shehab Eid; Cunjie Zhang; Wenda Zhao; Leo Xu; Eleanore Lin; et al. (PLoS ONE, 2025)
Any strategy that can selectively and persistently lower the brain levels of the cellular prion protein (PrP C ) is expected to extend survival in prion diseases. Recent advances in the virus-mediated delivery of gene therapies prompted us to explore if a recombinant adeno-associated virus (rAAV) vector delivering a CRISPR-Cas-based gene editor can be devised that induces a functional knockout of the prion gene. Whereas the eventual objective is to assess the therapeutic potency of an optimized vector in prion-infected mice, in this proof-of-concept study, we evaluated tools and methods that are suited to achieve this goal. The result of these efforts is a first-generation all-in-one rAAV vector that codes for a prion gene-specific guide RNA and a small Cas9 endonuclease, whose expression is controlled by a truncated neural cell adhesion molecule 1 (NCAM1) promoter that is active in PrP C expressing cells. We also constructed a second rAAV vector coding for a prion gene-specific ‘traffic light reporter’ (TLR). The TLR can be used to monitor prion gene-editing efficacy by coding for red and green fluorescent proteins separated by a segment of the prion gene that is targeted by the gene editor. For the purification of AAVs, we adopted a robust and scalable rAAV vector assembly pipeline and undertook proof-of-concept prion gene editing experiments in human cells and mice, which to date yielded prion gene editing rates of approximately 20% and 5%, respectively. Finally, we compared brain distributions of rAAV vectors following intrathalamic versus retro-orbital injection, and selected the 9P31 capsid for future studies based on a 7.5-fold higher heterologous gene expression level as compared to the PHP.eB capsid.